Development of Textbooks with a Contextual Approach Based on Local Wisdom: Product Validity Analysis - Bayo Angin, Toras Barita; Deka Maita Sandi; Marzuki Ahmad (Journal of Science and Education (JSE), 2024)
Improving creativity in writing descriptive essays among students is one of the challenges in learning Indonesian, especially when the teaching materials are not directly connected to the students' cultural background. Therefore, this study aims to develop and analyze the validity of contextual textbooks based on local wisdom in order to improve students' writing creativity. This study uses the Research and Development (R&D) method with the Plomp development model which includes the Preliminary research stage, Prototyping stage, Assessment phase. The validity of the textbook is analyzed through the aspects of content feasibility, presentation feasibility, language feasibility, approach feasibility. The research instrument is a validation sheet of the textbook product. There are 4 validators involved in the validation process. The results of the study indicate that the textbook developed has a high level of validity in the four dimensions, which include content feasibility of 84.47%, presentation feasibility of 88.33%, language feasibility of 88.00%, and approach feasibility of 87.68%. And overall, the average percentage value was 86.25%. Based on the validation results, it was concluded that the developed textbook product was in good criteria. The implications of this study indicate that the development of local wisdom-based textbooks is not only culturally relevant, but also feasible in encouraging students' creativity in writing descriptive essays. The obtained textbooks can be tested in the field so that the effectiveness and practicality of the developed textbook products are found.